Social skills training for children with Asperger syndrome and high-functioning autism - White, Susan Williams (New York : Guilford Press, 2011)
Explains how social skills training can be an important part of a comprehensive treatment program for children and adolescents with Asperger syndrome and high-functioning autism, and describes numerous approaches for designing interventions that fit each individual's needs.
Introduction -- Clinical evaluation and assessment of social skills -- Types of interventions and adaptations for ASD -- Social skills training groups -- Strategies for the classroom -- Strategies for the clinic -- Promoting social skills training at home -- Improving social competence beyond childhood.
Includes bibliographical references (pages 165-176) and index.
Keywords: Social skills -- Study and teaching; Asperger's syndrome; Autism in children; Asperger Syndrome -- rehabilitation; Autistic Disorder -- rehabilitation; Interpersonal Relations; Social Behavior; Child; Asperger's syndrome; Autism in children; Social skills -- Study and teaching